2016
DOI: 10.20960/nh.565
|View full text |Cite
|
Sign up to set email alerts
|

Bajos niveles de rendimiento físico, VO2MAX y elevada prevalencia de obesidad en escolares de 9 a 14 años de edad

Abstract: Introduction: Low levels of moderate and vigorous physical activity are a factor of important behavioral risk in the obesity in children. Objective: The objective of this study was to determine the nutritional status and physical condition of students, by comparing the results obtained by gender, obesity, and physical performance. Material and methods: 578 students; 308 men of 11.22 ± 1.93 years and 270 women of 10.93 ± 1.92 years, participated in the investigation. Were evaluated; body mass index (BMI), perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
0
0
2
Order By: Relevance
“…The results of the PF tests showed that obese subjects presented lower values than normal weight participants on tests that required acceleration of body mass. Hence, obese subjects had lower values of CRF compared to the other groups (in both girls and boys), which is similar to the findings described in former studies [22,[39][40][41]. Similarly, these results were comparable to other studies conducted in Spain [22,42,43], as well as in the Region of Murcia [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the PF tests showed that obese subjects presented lower values than normal weight participants on tests that required acceleration of body mass. Hence, obese subjects had lower values of CRF compared to the other groups (in both girls and boys), which is similar to the findings described in former studies [22,[39][40][41]. Similarly, these results were comparable to other studies conducted in Spain [22,42,43], as well as in the Region of Murcia [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…Además, la gran repercusión en la salud de las personas, hace que se intente tratar desde los primeros años de vida. Cabe resaltar, que una de las problemáticas y preocupaciones extendidas en el mundo en relación al sobrepeso son las cifras crecientes de obesidad infantil (Bacardí-Gascón, Jiménez-Cruz, Jones, y Guzmán, 2007). Los cálculos aproximados señalan que unos 250 millones de personas tienen obesidad en todo el mundo, enfatizando que con sobrepeso estarían el doble o el triple (Speiser, Rudolf y Anhalt, 2005).…”
Section: Palabras Claveunclassified
“…Para Navarrete et al, (2015) el perfil metabólico se determina por el comportamiento de parámetros clínicos y de composición corporal, así como el análisis de la frecuencia de actividad física y hábitos de vida saludable. Existen diferentes métodos para la evaluación del perfil metabólico, basado en la determinación de la alerta metabólica temprana (Chamorro et al, 2018), otros en base a la asociación del índice de masa corporal y relación cintura/estatura con la presión arterial (Diaz & Development, 2021), análisis antropométricos López et al (2020), análisis de pliegues cutáneos, perímetros corporales incluido el perímetro del cuello (Pedreros et al, 2018), métodos de bioempedancia (Dopsaj et al, 2021), entre otros.…”
Section: Introductionunclassified